2016
DOI: 10.1103/physrevlett.117.034501
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Saffman-Taylor Experiments with Particles Lead to Capillarity Driven Fingering Instabilities

Abstract: Using air to displace a viscous fluid contained in Hele-Shaw cell can create a fingering pattern at the interface between the fluids, if the capillary number exceeds a critical value. This SaffmanTaylor instability is revisited for the inverse case of a viscous fluid displacing air, when partially wettable hydrophilic particles are lying on the walls. Though the inverse case is otherwise stable, the presence of the particles results in a fingering instability at low capillary number. This capillarydriven insta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Such inverse Saffman-Taylor instabilities can occur when there are wettable particles present that can adsorb to the air/fluid interface. This adsorption, due to interfacial energy minimization, can induce interfacial instabilities 78 . It is known that bacteria can accumulate at interfaces 79 , and B. subtilis can form floating biofilms at air/water interfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Such inverse Saffman-Taylor instabilities can occur when there are wettable particles present that can adsorb to the air/fluid interface. This adsorption, due to interfacial energy minimization, can induce interfacial instabilities 78 . It is known that bacteria can accumulate at interfaces 79 , and B. subtilis can form floating biofilms at air/water interfaces.…”
Section: Discussionmentioning
confidence: 99%
“…There are many studies on the displacement in the porous media or Hele-Shaw cells under hydrodynamically unstable and stable conditions of the interface with and without chemical reactions [7,[11][12][13][14]. Although the unstable interfaces on the fully miscible and immiscible systems in hydrodynamically stable displacement have been reported by many papers, research on specialized conditions such as prewetting condition [15][16][17], including particles [18][19][20][21], viscosity-change reaction at the interface [22][23][24][25], precipitation reaction [26], and double diffusivity effect [27] is limited. Studies on the partially miscible system have recently received a lot of attention because of its application in enhanced oil recovery [5].…”
Section: Introductionmentioning
confidence: 99%
“…As a result viscous fingering has been shown to play a role in enhancing mixing at the interface of two fluids, however, the degree of mixing is highly dependent on the specific viscosity ratio 20 . In particular, it has also been shown that when the invading fluid is more viscous than the resident fluid, the front usually remains stable 21,22 reducing the mixing potential.…”
Section: Introductionmentioning
confidence: 99%